2014
DOI: 10.1016/j.biomaterials.2013.10.041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle agglomeration on the formation of a surface-connected compartment induced by hydroxyapatite nanoparticles in human monocyte-derived macrophages

Abstract: Agglomeration dramatically affects many aspects of nanoparticle–cell interactions. Here we show that hydroxyapatite nanoparticles formed large agglomerates in biological medium resulting in extensive particle uptake and dose-dependent cytotoxicity in human macrophages. Particle citration and/or the addition of the dispersant Darvan 7 dramatically reduced mean agglomerate sizes, the amount of particle uptake and concomitantly cytotoxicity. More surprisingly, agglomeration governed the mode of particle uptake. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 51 publications
5
73
0
Order By: Relevance
“…As a result the obtained size will be smaller. Unpredictable agglomeration happens in high concentrations unless surfactants are used [71]. On the contrary, using too dilute samples may not generate enough scattered light to analyze.…”
Section: Sample Concentrationmentioning
confidence: 98%
“…As a result the obtained size will be smaller. Unpredictable agglomeration happens in high concentrations unless surfactants are used [71]. On the contrary, using too dilute samples may not generate enough scattered light to analyze.…”
Section: Sample Concentrationmentioning
confidence: 98%
“…23,54 Synthetic hydroxyapatite particles with a fine needle shape or hydroxyapatite aggregate can activate the NLR (nucleotide-binding oligomerization domain receptors) family, pyrin domain-containing 3 inflammasome in lipopolysaccharide-induced macrophages, and can induce secretion of proinflammatory cytokines such as interleukin 1β and interleukin 18 in blood. 55,56 It has been shown that the mineral hydroxyapatite NPs exhibit significant dose-dependent cytotoxicity via human macrophages. 55,56 The protein corona can significantly influence NP-cell interactions through different internalization and pathway activations.…”
Section: Activated Immune Response By Protein Coronas General Recognimentioning
confidence: 99%
“…55,56 It has been shown that the mineral hydroxyapatite NPs exhibit significant dose-dependent cytotoxicity via human macrophages. 55,56 The protein corona can significantly influence NP-cell interactions through different internalization and pathway activations. 10 Selective cellular uptake of disulfidestabilized poly-(methacrylic acid) nanoporous polymer particles with presence and without presence of protein corona conditions was recently reported.…”
Section: Activated Immune Response By Protein Coronas General Recognimentioning
confidence: 99%
“…CaP based biomaterials, including α and β-TCP, hydroxyapatite (HA) and calcium sulphate, have been extensively used in orthopaedics as a bone substitute material 26,53,54 . Nanoparticles in a size range of 20-200 nm has been shown to be optimal for intracellular delivery, with bare CaP nanoparticles often undergoing significant levels of agglomeration leading to development of a much larger particle size over time [55][56][57][58] . Thus, currently CaP nanoparticles are largely used with modifications to increase their stability and to control their size in order to improve their capacity to cross the cell membrane 57 .…”
Section: Discussionmentioning
confidence: 99%